2019
DOI: 10.1080/02699052.2019.1607557
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-concussion-like symptoms in the general population in Italy, The Netherlands and the United Kingdom

Abstract: Objectives: To evaluate the frequency of post-concussion symptoms and prevalence and risk factors of post-concussion syndrome (PCS) in the general population, investigate the association between the Rivermead Post-Concussion Symptoms Questionnaire (RPQ) and self-perceived health, and evaluate differences between three European countries. Methods: A web-based survey including the RPQ and EQ-5D was conducted among representative samples in three European countries. Results: A total of 11,759 respondents complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 35 publications
2
40
0
1
Order By: Relevance
“…In studies on self-reported symptoms following TBI, women are more likely to report problems across different symptom domains [14]. Furthermore, post-concussion symptoms and especially fatigue is prevalent in the general population as well [37]. However, previous research has suggested that gender differences in socialization and gender-role expectations may change over time and moderate the relationship between gender and outcome measures after TBI [9,25].…”
Section: Discussionmentioning
confidence: 99%
“…In studies on self-reported symptoms following TBI, women are more likely to report problems across different symptom domains [14]. Furthermore, post-concussion symptoms and especially fatigue is prevalent in the general population as well [37]. However, previous research has suggested that gender differences in socialization and gender-role expectations may change over time and moderate the relationship between gender and outcome measures after TBI [9,25].…”
Section: Discussionmentioning
confidence: 99%
“…All respondents reported PCS symptoms; however, the median total score of the sample was 13 (the first quartile was 11, and the third was 17). This compares to a median score of eight (the first quartile was zero, and the third was 22) in the general population of the UK using the same measure (not taking brain injury into account) [76]. The majority of participants had already left education at the time of interview (67.3%, N=66), and of these most left in secondary school at the mean age of 14.34 years (SD 1.63).…”
Section: Participants' Demographic and Clinical Characteristicsmentioning
confidence: 89%
“…In previous research, contradictions in reporting differences regarding post-concussion symptom and syndrome following complicated and uncomplicated mTBI has led to a conundrum, which is based on the question if patients after complicated mTBI are similar or dissimilar based on symptom reporting compared to uncomplicated mTBI patients. Furthermore, the discussion still stands if post-concussion symptoms are TBI specific [31] and regarding the existence of post-concussion syndrome [4,32,33]. There is no gold standard regarding defining PCS and which severity rating should be used as a cut-off [26], and different approaches to analysis, classification and quantification of PCS exist and lead to variability in results [26].…”
Section: Discussionmentioning
confidence: 99%